(untitled) (Journal of Mathematical Study, 2014)
Let {X_n,n≥1} be a sequence of negatively superadditive dependent (NSD, in short) random variables and {a_nk, 1≤ k≤ n, n≥1} be an array of real numbers. Under some suitable conditions, we present some results on complete convergence for weighted sums _k=1^na_nkX_k of NSD random variables by using the Rosenthal type inequality. The results obtained in the paper generalize some corresponding ones for independent random variables and negatively associated random variables.